Overview of HbsAg Testing Results for Chronic Kidney Disease Patients Undergoing Hemodialysis at Ciamis Hospital - Suryadi, Tison; Setiawan, Doni; Solihah, Lili; Ruhimat, Undang; Ariyadi, Rivana (LPPM STIKes Muhammadiyah Ciamis, 2024)
Background & Objective: Chronic renal failure is a slow and incurable disease. Regular treatment can halt the deterioration of kidney function, with kidney transplantation and hemodialysis being the most common options. However, hemodialysis patients are at risk of contracting the Hepatitis B virus due to the use of repeated vascular access and high frequency of hemodialysis. This study aims to describe the results of HBsAg examination in patients with chronic renal failure who undergo hemodialysis. Method: The research is a descriptive study that used a purposive sampling technique and was conducted in May-June 2022. The study included 44 chronic renal failure patients who underwent HBsAg examination using the Immunochromatography method. Result: The study's results showed that all 44 respondents (100%) who underwent hemodialysis had negative HBsAg examination results, indicating that they were not exposed to the Hepatitis B virus. Conclusion: In conclusion, the study indicates that chronic renal failure patients undergoing hemodialysis are not at risk of contracting the Hepatitis B virus. Further research could include quantitative Hepatitis B antibody examinations.